Estudo in vitro de técnicas de instrumentação mecanizada e medicações intracanais como propostas de protocolos para pulpectomia em dentes decíduos - Chrisostomo, Daniela Alvim [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
This thesis was divided into 2 scientific articles. The article 1 aimed to compare two endodontic instrumentation protocols with rotary or reciprocating files, performed on prototypes of primary molars using microcomputed tomography (micro-CT); and article 2 aimed to evaluate the effect of two proposed intracanal medications: triantibiotic combination (TRI) of metronidazole, ciprofloxacin and fosfomycin (FOSFO) and the association of epigallocatechin gallate (EGCG) with FOSFO, in comparison with the controls calcium hydroxide paste (CH) or chlorhexidine (CHX), all dissolved in polyethylene glycol 400 (PEG) in multispecies biofilms, toxicity in fibroblasts and collagenolytic and gelatinolytic activities detected in root dentin. For the methodology of article 1, 24 3D printed prototypes of artificial deciduous molars were used, which were distributed into two groups of 12 each, according to the type of instrumentation: with Sequence Baby NiTi files© (SBF) rotary files or reciprocating files with X1-Blue File NiTi© (XBF). The following parameters were evaluated: root canal and dentin volumes, canal transportation and centralization, risk of root perforation and instrumentation time. For the methodology of article 2, the antibiofilm effect and cytotoxicity of drugs containing a combination of antibiotics, EGCG+FOSFO or CH were evaluated in multispecies biofilms formed in root dentin samples by confocal microscopy and in fibroblast cells by resazurin assays, respectively. Inhibition of protease activity by drugs was measured by collagenolytic enzyme activity assays (ELISA) and gelatinolytic activity by metalloproteinases - MMP with in situ zymography in radicular dentin specimens. The results of article 1 showed that SBF promoted less enlargement of the root canal and consequently removed less dentin when compared to the reciprocating system. In general, both instrumentation protocols showed no statistical difference between them considering root canal transport and centralization capacity. There was no difference in dentin thickness, fractures and fissures comparing the pre- and postoperative moments for both endodontic systems. Instrumentation time was shorter for XBF. The results of article 2 showed that EGCG+FOSFO, combination of antibiotics and CH in PEG 400 significantly reduced bacteria from multispecies biofilms in dentinal tubules and at lower concentrations were not toxic to fibroblasts. All drugs showed anticollagenolytic activity compared to PEG and water. PEG+CH and PEG+CHX decreased the in situ gelatinolytic activity of MMP when compared to the untreated control. PEG+TRI increased gelatinolytic activity in root dentin. In conclusion, both endodontic instrumentation protocols were safe to be used in pulpectomy of primary teeth, as they promoted a minimum reduction in dentin volume, transport and decentralization of the canal, and consequently mitigated changes in dentin thickness and the possibility of fractures. Although instrumentation time was shorter for the reciprocating system, it caused a greater increase in canal volume. EGCG+FOSFO contained in PEG-400 showed antibiofilm and anticolagenolytic properties, in addition to low cytotoxicity at lower concentrations, and could be an alternative intracanal medication for endodontic purposes.

Esta tese foi dividida em 2 artigos científicos. O artigo 1 teve como objetivo comparar dois protocolos de instrumentação endodôntica com limas rotatórias ou com limas reciprocantes, realizados em protótipos de molares decíduos por meio de microtomografia computadorizada (micro-CT); e o artigo 2 teve como objetivo avaliar o efeito de duas propostas de medicações intracanais: combinação triantibiótica (TRI) de metronidazol, ciprofloxacina e fosfomicina (FOSFO), e a associação de epigalocatequina-3-galato (EGCG) com FOSFO, em comparação com os controles pasta de hidróxido de cálcio (CH) ou clorexidina (CHX), todos dissolvidos em polietilenoglicol-400 (PEG) em biofilmes multiespécies, toxicidade em fibroblastos e atividades colagenolíticas e gelatinolíticas detectadas na dentina radicular. Para a metodologia do artigo 1 foram utilizados 24 protótipos impressos em 3D de molares decíduos artificiais que foram distribuídos em dois grupos de 12 cada, de acordo com o tipo de instrumentação: com limas rotatórias Sequence Baby File NiTi© (SBF) ou limas reciprocantes com limas X1-Blue File NiTi© (XBF). Foram avaliados os parâmetros: volumes do canal radicular e da dentina, transporte e centralização do canal, risco de perfuração radicular e tempo de instrumentação. Para a metodologia do artigo 2, o efeito antibiofilme e a citotoxicidade de medicamentos contendo combinação de antibióticos, EGCG+FOSFO ou CH foram avaliados em biofilmes multiespécies formados em amostras de dentina radicular por microscopia confocal e em células de fibroblastos por ensaios de resazurina, respectivamente. A inibição da atividade das proteases por medicamentos foi medida por ensaios de atividade enzimática colagenolítica (ELISA) e atividade gelatinolítica por metaloproteinases - MMP com zimografia in situ em espécimes de dentina radicular. Os resultados do artigo 1 mostraram que o SBF promoveu menor alargamento do canal radicular e consequentemente removeu menos dentina quando comparado ao sistema reciprocante. De modo geral, ambos os protocolos de instrumentação não apresentaram diferença estatística entre si considerando o transporte do canal radicular e a capacidade de centralização. Não houve diferença na espessura da dentina, fraturas e fissuras comparando os momentos pré e pós-operatórios para ambos os sistemas endodônticos. O tempo de instrumentação foi menor para XBF. Os resultados do artigo 2 mostraram que EGCG+FOSFO, combinação de antibióticos e CH em PEG 400 reduziram significativamente as bactérias dos biofilmes multiespécies nos túbulos dentinários e em concentrações mais baixas não foram tóxicos para os fibroblastos. Todos os medicamentos apresentaram atividade anticolagenolítica em comparação ao PEG e à água. PEG+CH e PEG+CHX diminuíram a atividade gelatinolítica in situ da MMP quando comparado ao controle sem tratamento. PEG+TRI aumentou a atividade gelatinolítica na dentina radicular. Concluindo, ambos os protocolos de instrumentação endodôntica foram seguros para serem utilizados em pulpectomia de dentes decíduos, pois promoveram mínima redução do volume dentinário, transporte e descentralização do canal, e consequentemente amenizaram alterações na espessura dentinária e as possibilidades de fraturas. Embora o tempo de instrumentação tenha sido menor para o sistema reciprocante, ele causou maior aumento no volume do canal. EGCG+FOSFO contidos no PEG-400 apresentou propriedades antibiofilme e anticolagenolíticas, além de baixa citotoxicidade em concentrações mais baixas, podendo ser uma alternativa de medicação intracanal para fins endodônticos.
In vitro study of mechanized instrumentation techniques and intracanal medications as protocols proposed for pulpectomy in primary teeth
Keywords: Pulpectomia; Instrumentos odontológicos; Antibacterianos; Anti-infecciosos; Biofilmes; Metaloproteases; Dentes decíduos; Pulpectomy